Primary leiomyosarcoma of the fallopian tube: Three case reports and review of the literature - Ling-fang Xia; Shuang Ye; Xu-xia Shen; Jia Tang; Hui-juan Yang; Yan Huang (Elsevier, 2018)
Objective: Leiomyosarcoma of the fallopian tube is a rare malignant gynecologic neoplasm with poor prognosis. It is important to share experience and to collect more cases to improve the understanding of the disease. Case report: We reported three patients with leiomyosarcoma of the fallopian tube who were treated in Fudan University Shanghai Cancer Center (Shanghai, China) from 2012 to 2016. Although the three cases shared the same diagnosis, they varied in the presentations, treatments, and outcomes. Conclusion: Leiomyosarcoma of the fallopian tube seems to have some particularities in imaging manifestations and immunohistochemical results. It has a progressive course with limited therapeutic options such as surgery, chemotherapy or radiotherapy.